2021
DOI: 10.1093/jme/tjab014
|View full text |Cite
|
Sign up to set email alerts
|

Relative Roles of Blow Flies (Diptera: Calliphoridae) and Invasive Fire Ants (Hymenoptera: Formicidae:Solenopsisspp.) in Carrion Decomposition

Abstract: Fire ants (Solenopsis spp.) have increasingly been reported from carrion in the southeastern United States and are now a part of the normal succession community. There have been previous observations of these ants altering carrion and preying on other carrion-attendant fauna; however, the overall effects of these activities on carrion decomposition rates, community composition, and blow fly larval development are poorly understood. Alteration of these ecological processes by fire ants could affect the forensic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…2a), prevented not only the landing, and continuous oviposition/larviposition by flies, but also, the formation of large maggot masses on the carcass. This observation is consistent with the findings of other similar studies [11,16,33]. In the mid-and late autumn trials (May 2021), several individuals of Crematogaster cf.…”
Section: Predatory Activity: Prevention Of Continuous Fly Landing And...supporting
confidence: 93%
“…2a), prevented not only the landing, and continuous oviposition/larviposition by flies, but also, the formation of large maggot masses on the carcass. This observation is consistent with the findings of other similar studies [11,16,33]. In the mid-and late autumn trials (May 2021), several individuals of Crematogaster cf.…”
Section: Predatory Activity: Prevention Of Continuous Fly Landing And...supporting
confidence: 93%
“…Invertebrates are the determinant group responsible for the decomposition of animal carcasses in many natural ecosystems (Benbow et al, 2019; Johnson, 1975). The ants, the most abundant terrestrial insect group in the world (Davidson, 1997; King et al, 2013), are always observed to visit carrion for food, directly and/or indirectly affecting carrion decomposition (De Jong et al, 2021; Eubanks et al, 2019; Paula et al, 2016). Consistent with our hypothesis, we demonstrated here that C. herculeanus delayed the decomposition of yak carrion by predating on Diptera larvae that were responsible for carrion decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…Studies directly addressing the influence of ants on vertebrate carrion decomposition are scarce and provide conflicting conclusions. The skin lesions created by ants could potentially accelerate the decomposition process by causing epidermal ripping during the bloating stage, thereby providing quicker access for other insects to the inside of carcasses 17 19 . In contrast, the presence of ants could exclude insect decomposers from the carcass or predate larval and adult flies; predation of carrion feeding insects has been shown to decelerate decomposition rates 3 , 20 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Lindgren et al 23 documented a behavior exhibited by the red imported fire ant ( Solenopsis invicta ) in which nest-like structures were built directly on the surface of the corpse, leading to an eight-day delay of blow fly colonization. Other studies have investigated the effect of fire ants on invertebrate decomposers and found that the presence of fire ants effectively excluded flies and beetles from mouse carcasses 19 , 21 .…”
Section: Introductionmentioning
confidence: 99%